1974
DOI: 10.1111/j.1365-2621.1974.tb02914.x
|View full text |Cite
|
Sign up to set email alerts
|

Application of Sds‐acrylamide Gel Electrophoresis for Determination of the Maximum Temperature to Which Bovine Muscles Have Been Cooked

Abstract: The sodium dodecylsulfate‐acrylamide gel electrophoresis was evaluated as a method to determine the cooking temperature to which beef has been cooked. Water soluble protein extracts from bovine muscles cooked to the final temperatures of 65, 70, 75, 80, 85 and 90°C were applied on SDS‐acrylamide gels. The extracts showed characteristic electrophoretic patterns for each cooking temperature examined. The thermoprofiles were highly reproducible among a number of experimental variables. The high degree of accuracy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

1979
1979
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 7 publications
0
19
0
Order By: Relevance
“…An advantage of using SDS‐PAGE is that it enables constant electrophoretic mobilities of proteins, independent of isoelectric point and amino acid composition, which can be slightly modified during cooking. 10 Figure 1 illustrates SDS‐PAGE patterns of the proteins extracted with 0.9% NaCl solution from heated blue marlin meats which were heated at different temperatures with different holding times. Analysis of the raw meat revealed approximately 10 protein bands with molecular weights calculated between 23 and 87 kDa.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An advantage of using SDS‐PAGE is that it enables constant electrophoretic mobilities of proteins, independent of isoelectric point and amino acid composition, which can be slightly modified during cooking. 10 Figure 1 illustrates SDS‐PAGE patterns of the proteins extracted with 0.9% NaCl solution from heated blue marlin meats which were heated at different temperatures with different holding times. Analysis of the raw meat revealed approximately 10 protein bands with molecular weights calculated between 23 and 87 kDa.…”
Section: Resultsmentioning
confidence: 99%
“…Activities of MDH and LDH in fresh turkey meat were both observed to decline sharply between 72 and 74°C, while in cured turkey breast the activity was lost over a broader range of 70 to 74°C. Lee et al employed sodium dodecylsulfate‐polyacrylamide gel electrophoresis (SDS‐PAGE) in the study of qualitative changes in electrophoretic patterns of low‐salt soluble proteins 10 to assess the final cooking temperature. 11 Differential scanning calorimetry (DSC) has been also used to investigate the denaturation of meat proteins 11–13 and to estimate the maximum cooking temperature of meat products.…”
Section: Introductionmentioning
confidence: 99%
“…An advantage of using SDS-PAGE is that it enables constant electrophoretic mobilities of proteins, independent of isoelectric point and amino acid composition, which can be slightly modified during cooking. 11 Figure 1 illustrates SDS-PAGE patterns of the proteins extracted with 0.9% NaCl solution from skipjack tuna meat heated at dif-ferent temperatures with different holding times. Analysis of the unheated skipjack tuna meat revealed approximately 12 protein bands with the molecular mass estimated between 15 and 87 kDa.…”
Section: Determination Of End-point Temperature By Sds-pagementioning
confidence: 99%
“…A large number of studies have been conducted to determine the previous heat treatment (end‐point temperature; EPT) of meat products, 5–11 but similar studies on marine products are almost negligible. In our previous study, 12 it was revealed that the coagulation test was able to predict EPT of heated blue marlin meat up to 67°C, which was also confirmed by sodium dodecylsulfate polyacrylamide gel electrophoresis (SDS‐PAGE) and enzyme activity determination.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation